Effect of Complex Structural Material Coated the Flight Body to Measure the Absorption of Radar Radiation at Different Elevations of Flight Latitude - Ali Mhmood Karwi, Abbas (International Journal of Engineering and Technology, 2018)
Avoiding radar detection is a prime importance in several fields. We design multi reinforced polymeric materials to absorb radar waves, these materials have low density, high elastic modulus, high tensile strength good erosion resistance and good fatigue strength. Composite materials are made by three principle techniques, injection, spraying and compression. Jet technique was used to measure materials resistance for erosion. We find that  polytetrafluroethylene with multi mixtures  has the best specification than other polymeric materials. We manufacture twenty-one alloys (A, B, C, D, E, F…..W) used in this work. Composite materials (A-W) are making by adding fillers to matrices. Absorption coefficient of fillers and matrices was evaluated and measured alone or as a composite. Dynamic and static radar cross section shapes (eight shapes)were studied in this work. The better shapes for absorption waves are (spherical, conical, cylindrical, and parabolic). All parameters controlled reflectivity and absorption were studied. We found that the maximum rate of absorption is more than (70%), this percent observed in certain coating layers. Metallurgical and mechanical work on composite materials have been investigated. Model designed to compute multi variables affecting on absorption and reflection.